The role of transforaminal percutaneous endoscopic discectomy in lumbar disc herniations - Gotecha, Sarang (J Craniovertebr Junction Spine, 2016)
OBJECTIVES: To study 1)the efficacy of transforaminal percutaneous endoscopic lumbar discectomy in lumbar disc herniations.2) limitations and advantages of the surgical procedure. 3)morbidity and complications associated with the procedure. MATERIALS AND METHODS: This study was carried out on 120 patients who had single level herniated disc Pre-operative assessment of VAS and MSS scoring systems were documented one day prior to surgery. Post operative results were determined by MacNab criteria and by modified Suezawa and Schreiber clinical scoring system (MSS score). RESULTS: Maximum patients were in the age group of 31 to 40 years and 83.43% of the patients were males. 80% patients had lumbar disc herniation at L4-L5 level, The mean operative time of endoscopic discectomy was 52.28 minutes and the mean hospital stay was 2.1days.8 cases of L5-S I were abandoned due to high iliac bone and hence their disc could not be accessed. Out of 112 patients who underwent operation, 2 patients developed discitis and 1 was found to have dysesthesia. Also recurrent prolapsed intervertebral disc was seen in 6 cases The mean preoperative and 6 months follow-up VAS score was 8.4 and 1.89 respectively. Mean preoperative and 6 months follow-up Modified Suezawa And Schreiber Clinical Scoring System(MSS Score) was 3.47 and 7.92 respectively. MSS score showed excellent and good outcome in 82.12% patients and Modified Macnab Criteria showed excellent and good outcome in 89.3% patients at 6months follow-up. CONCLUSION: TPELD can be a reasonable alternative to conventional microscopic discectomy for the treatment of patients with LDH. We also conclude that TPELD is not an effective procedure for L5-S 1 disc and an open procedure should be opted for better outcomes.